Efeito do extrato insaponificável de abacate e soja na doença periodontal induzida, na osseointegração de implantes e no reparo de defeitos críticos de calvaria de ratos - Oliveira, Guilherme José Pimentel Lopes de [UNESP] (2014)
The aim of this study was to evaluate in rats the effect of the avocado soybean unsaponifiables (ASU) on the bone repair in induced periodontitis, on the osseointegration of dental implants, and on the repair of the critical sized calvaria defects filled or no with biomaterials. For this purpose, the following hypothesis regarding the use of ASU were tested: 1)Improve the periodontal repair in induced periodontitis; 2)Improve the periodontal repair after the treatment of the induced periodontitis; 3) Accelerate osseointegration; 4) Improve the integration of osteoconductors bone grafts in the critical size calvaria defects. For the evaluation of the first hypothesis, eighty-four animals were randomly assigned into four equally-sized groups, receiving daily by gavage either sterile saline (CTR) or ASU (0.6 mg/kg), starting either 7 days prior to- (ASU/-7), or on the day- (ASU/0), or 7 days after (ASU/+7) periodontitis induction. Periodontitis was induced by placing silk ligatures into the gingival sulcus of the second maxillary molars for 7 days; thereafter the ligatures were removed. Seven animals from each group were euthanized at 7, 15 or 30 days after ligature removal. Bone resorption was evaluated by histomorphometry and micro CT. Immunohistochemistry was used to evaluate TRAP, RANKL, Alkaline phosphatase and qPCR to evaluate IL-1β, TNF-α, IL-6, RANKL, Alkaline phosphatase (AP). For the evaluation of the second hypothesis, periodontitis was induced in 84 rats via ligature placement around the second upper molar, which was removed after 7 days, and scaling was performed at this time. Subsequently, the rats were randomly allocated to four groups with 21 animals each: One in which saline solution (SS) was administered (SRP) and three in which ASU was administered (0.6 g/kg/day), beginning either 7 days before the induction of periodontitis (SRP/ASU-7), on the day of periodontitis induction (SRP/ASU0), or on the day of treatment...